2019
DOI: 10.1038/s41387-019-0099-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharide (GO2KA1) improves postprandial glycemic response in subjects with impaired glucose tolerance and impaired fasting glucose and in healthy subjects: a crossover, randomized controlled trial

Abstract: BackgroundThe antidiabetic and hypoglycemic effects of chitosan have been reported in previous studies. We have previously shown that chitosan oligosaccharide reduces postprandial blood glucose levels in vivo. We conducted a short-term crossover study to support the results of the previous study.MethodsThe study was a randomized, double-blind, controlled crossover trial completed at one clinical research site. Subjects with impaired glucose tolerance and impaired fasting glucose and healthy subjects were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In a recent randomized, controlled, double-blind, crossover clinical trial, the administration of chitosan oligosaccharides could reduce postprandial blood glucose levels in the 2-h oral sucrose tolerance test (OSTT), suggesting the improvement of impaired glucose tolerance [ 78 ]. Similarly, chitosan has reduced gluconeogenesis-related signals (e.g., PEPCK (phosphoenolpyruvate carboxykinase), p38, and AMPK), increased muscle glucose uptake-related signals (e.g., Akt), and promoted glucose transporter-4 (GLUT4) translocation from cytoplasm to membranes in streptozotocin-induced diabetic rats.…”
Section: Biological Effects Of Chitosan and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent randomized, controlled, double-blind, crossover clinical trial, the administration of chitosan oligosaccharides could reduce postprandial blood glucose levels in the 2-h oral sucrose tolerance test (OSTT), suggesting the improvement of impaired glucose tolerance [ 78 ]. Similarly, chitosan has reduced gluconeogenesis-related signals (e.g., PEPCK (phosphoenolpyruvate carboxykinase), p38, and AMPK), increased muscle glucose uptake-related signals (e.g., Akt), and promoted glucose transporter-4 (GLUT4) translocation from cytoplasm to membranes in streptozotocin-induced diabetic rats.…”
Section: Biological Effects Of Chitosan and Its Derivativesmentioning
confidence: 99%
“…In a recent clinical trial, after the administration of chitosan oligosaccharide (GO2KA1, a code name of chitosan oligosaccharide), it showed a decreasing trend in body fat ratios and waist circumferences, serum glucose levels, HbA1c (Hemoglobin A1c, a subtype of glycosylated hemoglobin), and C peptides (a byproduct in the formation of insulin) [ 89 ]. In addition, chitosan oligosaccharide (GO2KA1) could improve the impaired glucose tolerance and fasting glucose levels in a crossover, randomized, controlled clinical trial [ 78 ]. A meta-analysis indicates that chitosan treatment for patients significantly decreases DBP (diastolic blood pressure) in short-term interventions [ 90 ].…”
Section: Biological Effects Of Chitosan and Its Derivativesmentioning
confidence: 99%
“…GO2KA1 has been used in clinical trials. It was found that GO2KA1 effectively reduced postprandial blood glucose levels in subjects with impaired glucose tolerance and impaired fasting glucose [ 149 ]. However, it remains unclear whether chitosan oligosaccharide has a direct or indirect antidiabetic effect.…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%
“…A study also have shown that chitosan can improve lipid metabolism related to diabetes [36]. Many researchers have focused on the combined, synergistic, or additive effects of these molecules to treat this complex metabolic disorder [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Although the potential hypoglycemic effect of chitosan has been evaluated in clinical trials, these studies substantially vary with respect to the research design, population characteristics, chitosan supplement dosage, and duration, leading to mixed results and conclusions [ 29 , 31 34 , 37 , 39 – 43 ]. No systematic review or meta-analysis has been conducted to evaluate the effect of chitosan on human glycemic levels.…”
Section: Introductionmentioning
confidence: 99%